Interpretação fonológica e realização fonética durante o aprendizado de uma LE (Revista de Estudos da Linguagem, 2004)
In the process of learning a foreign language, the individual must master a new phonetic discourse formation and its respective reception in that language, according to the “rules” of the intermediary system of paradigmatic units which are not similar tophonemes either of the first or the second system. These special units have a mixed character that differentiates them from a free variation. They can be called diaphonemes, if we understand tha tthese units, which have a double character, become manifest inrelation to the intermediary linguistic system and show themselves to be paradigmatic units. Nevertheless, in relation to the system of language that is studied, they show themselves to be syntagmatic units, and their variations are the realizations of the phonemes of the idiom in question.